Two pairs of phenylpropanoid enantiomers from the leaves of Eucommia ulmoides. Issue 11 (2nd November 2018) - Shi, Xu-Liu; Yan, Jian-Kun; Li, Wen-Kai; Donkor, Paul Owusu; Gao, Xiu-Mei; Ding, Li-Qin; Qiu, Feng
Abstract: Two pairs of phenylpropanoid enantiomers, (+)-(7 S, 8 S )-alatusol D (1a ), (−)-(7 R, 8 R )-alatusol D (1b ), (−)-(7 S, 8 R )-alatusol D (2a ) and (+)-(7 R, 8 S )-alatusol D (2b ) were isolated from the leaves of Eucommia ulmoides Oliver. Among them, 1a and2b were firstly obtained by chiral enantiomeric resolution. Their structures were elucidated based on extensive spectroscopic analysis and the induced CD (ICD) spectrum caused by adding Mo2 (AcO)4 in DMSO. All compounds were tested on Hep G2 tumor cell lines. However, none of the compounds showed potential cytotoxic activity against Hep G2 in vitro . Abstract :